A New Computational Technique for Common Solutions between Systems of Generalized Mixed Equilibrium and Fixed Point Problems - Pongsakorn Sunthrayuth; Poom Kumam (Journal of Applied Mathematics)
We introduce a new iterative algorithm for finding a common element of a fixed point problem of amenable semigroups of nonexpansive mappings, the set solutions of a system of a general system of generalized equilibria in a real Hilbert space. Then, we prove the strong convergence of the proposed iterative algorithm to a common element of the above three sets under some suitable conditions. As applications, at the end of the paper, we apply our results to find the minimum-norm solutions which solve some quadratic minimization problems. The results obtained in this paper extend and improve many recent ones announced by many others.